2012
DOI: 10.1590/s0101-31222012000200009
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated aging of ipê seeds under controlled conditions of storage

Abstract: -This research was aimed at studying effects of storage and accelerated aging on germination and profile of storage proteins in Handroanthus albus seeds. These were stored into a cold chamber (± 8 o C; RH ± 40%) and after periods of 0, 3, 6, 9, and 12 months of storage, were subjected to accelerated aging for 0, 24, 48, 72, and 96 hours. Relationships between germination and proteins profile were assessed. Germination test was performed at 25 °C, under constant light. For protein extraction, 125 mg of seeds we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…Handroanthus impetiginosus seed germination presented fluctuations during storage and artificial aging, as observed by Carvalho et al (1976), Kano et al (1978), Maeda and Matthes (1984), , Figliolia et al (1988), Cunha et al (1992), Kageyama et al (1992), Mello and Eira (1995), Gemaque (1999) and Shibata et al (2012). Increases in H. impetiginosus seed germination during storage were detected by Carvalho et al (1976) at 63 days of storage, Kano et al (1978) at 300 days, at 240 days and Mello and Eira (1995) at 540 days.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Handroanthus impetiginosus seed germination presented fluctuations during storage and artificial aging, as observed by Carvalho et al (1976), Kano et al (1978), Maeda and Matthes (1984), , Figliolia et al (1988), Cunha et al (1992), Kageyama et al (1992), Mello and Eira (1995), Gemaque (1999) and Shibata et al (2012). Increases in H. impetiginosus seed germination during storage were detected by Carvalho et al (1976) at 63 days of storage, Kano et al (1978) at 300 days, at 240 days and Mello and Eira (1995) at 540 days.…”
Section: Discussionmentioning
confidence: 68%
“…From the results obtained in this study it can be assumed that other factors, like heat shock proteins, regulate H. impetiginosus seed germination during storage and artificial aging, and more consistent studies are needed in different phases of seed development and germination of this species. In a study conducted by Shibata et al (2012) was concluded that germination of H. albus seeds, when not subjected to accelerated aging, is favored by storage in cold chamber during three to six months, or from nine to 12 months when subjected to accelerated aging process, and storage proteins may be associated to those increases.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors reported that the degradation of proteins in stored seeds of red clover (Trifolium incarnatum) and perennial ryegrass (Lolium perenne) was dependent on the severity of the storage conditions (Ching & Schoolcraft, 1968). The decrease in the intensity of bands was also observed in seeds of tree species yellow ipe (Handroanthus albus) after storage for 12 months in cold chamber, followed by artificial aging (Shibata, Coelho, Oliveira, & Garcia, 2012).…”
Section: Discussionmentioning
confidence: 92%
“…Ghasemnezhad and Honermeier (2007) also observed protein degradation during storage of sunflower seeds, which suggests that protein intake occurred with the release of amino acids for consumption on metabolic activity and respiration of the seeds. Changes in protein content were also associated with germination during storage of Handroanthus albus seeds, although further studies are still needed; thus, it can be inferred that reserve proteins may be associated with seed viability (Shibata et al, 2012).…”
Section: Resultsmentioning
confidence: 99%